Pengaruh Kualitas Pelayanan terhadap Kepuasan Nasabah pada Cu Daya lestari TP. Kalaang Lawaat di Kabupaten Kutai Barat Kecamatan Barong tongkok - Ida Rahmawati3, Yoyo Eddy Soegiarto 2 (EKONOMIA, 2020)
Effects of Service Quality on Customer Satisfaction at CU Daya Lestari  TP. Kalaang Lawaat in West Kutai District, Barong Tongkok Sub-district, under the guidance of Mr.  H.  Eddy  Soegiarto K and Mrs.  Ida  Rahmawati.     The background of this research is the importance of good services. It is expected that the customers are satisfied and they will return to use the company products which meet their expectations. Therefore, the information technology and openness of the company play an important role to the customers. With the current good services, it is expected that CU Daya Lestari will always improve its services to provide satisfaction to all loyal customers.The research problem is to determine the effects of service quality consisting of tangibility, reliability, responsiveness, assurance, and empathy, at CU Daya Lestari TP. Kalaang Lawaat to the customer satisfaction in West Kutai District, Barong Tongkok Sub-district. The analysis tools in this study were test instrument, data of validity and reliability test. There classic assumption test used normality test, multicollinearity test, heteroskedasticity test, and autocorrelation test, as well as multiple linear regression analysis, hypothesis test, t test, f test, and coefficient of determination used SPSS 21.0.The result indicates that the variables of service quality consisting of tangibility, reliability, responsiveness, assurance, and empathy give significant effects on customer satisfaction. Tangibility, reliability, and assurance give positive effects and do not significant to customer satisfaction, while responsiveness and empathy give positive effects and significant to customer satisfaction at  CU Daya Lestari TP.  Kalaang  Lawaat  in  West  KutaiDistrict  ,Barong  Tongkok  Sub-district